Many Labs 5: Registered Replication of Crosby, Monin, and Richardson (2008). Issue 3 (September 2020) - Rabagliati, Hugh; Corley, Martin; Dering, Benjamin; Hancock, Peter J. B.; King, Josiah P. J.; Levitan, Carmel A.; Loy, Jia E.; Millen, Ailsa E.
Crosby, Monin, and Richardson (2008) found that hearing an offensive remark caused subjects ( N = 25) to look longer at a potentially offended person, but only if that person could hear the remark. On the basis of this result, they argued that people use social referencing to assess the offensiveness. However, in a direct replication in the Reproducibility Project: Psychology, the result for Crosby et al.'s key effect was not significant. In the current project, we tested whether the size of the social-referencing effect might be increased by a peer-reviewed and preregistered protocol manipulation in which some participants were given context to understand why the remark was potentially offensive. Three labs in Europe and the United States ( N = 283) took part. The protocol manipulation did not affect the size of the social-referencing effect. However, we did replicate the original effect reported by Crosby et al., albeit with a much smaller effect size. We discuss these results in the context of ongoing debates about how replication attempts should treat statistical power and contextual sensitivity.